The Social Thought in Socrates’ Philosophy - Warda Idan Bader, Researcher; Hamid Hamzah Al- Dulaimi, Prof. Dr. (lark, 2022)
Socrates was a Greek philosopher who was interested in man and society, shifting his focus away from the search for existence and toward the search for the man himself. And that the Sophists had done so before him, but when he was moved by the great wisdom of the Temple of Delphi, "Know yourself for yourself," he looked deeper into man’s core, i.e. himself. He preached a reformist message, emphasizing the need for wisdom and education in improving people’s lives. He represented a reformer tendency independent of religious extremism, sophist philosophy, and the terrible socioeconomic situation that Greek society was experiencing at the time. Socrates despised numerous sophistic beliefs and doctrines that were influencing young people’s minds and driving them to ignorance, as well as everything else that was changing. Socrates was able to earn people’s love because he was connected to them despite the simplicity in which he lived. He urged for unchanging ideals and colleges that are not subject to change, reforming the youth and leading society. After all, he was able to discriminate between good and evil through his guiding remarks, in which he invited them to know themselves rather than what others say is good or bad, such as riches or social status, or death, disease, or social rejection. Socrates has approached society’s problems from two perspectives: the first is a psychological orientation, and the second is a social orientation